2016
DOI: 10.1097/md.0000000000004445
|View full text |Cite
|
Sign up to set email alerts
|

Pain related to robotic cholecystectomy with lower abdominal ports

Abstract: Background:Robotic cholecystectomy (RC) using port sites in the lower abdominal area (T12-L1) rather than the upper abdomen has recently been introduced as an alternative procedure for laparoscopic cholecystectomy. Therefore, we investigated the time course of different components of pain and the analgesic effect of the bilateral ultrasound-guided split injection technique for rectus sheath block (sRSB) after RC in female patients.Methods:We randomly assigned 40 patients to undergo ultrasound-guided sRSB (RSB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…[ 15 ] In the present study and in Bakshis study, [ 13 ] the RSB injections were readministered at every 4 h indicating that the 8 h dosing interval in Padmanabhan's study [ 15 ] may have been too long to provide constant analgesic efficacy. In agreement with our data, Kim et al [ 16 ] found no opioid sparing efficacy and pain scores were lower only at 1 h after a single-dose RSB block but not thereafter compared with control group with no block.…”
Section: Discussionsupporting
confidence: 93%
“…[ 15 ] In the present study and in Bakshis study, [ 13 ] the RSB injections were readministered at every 4 h indicating that the 8 h dosing interval in Padmanabhan's study [ 15 ] may have been too long to provide constant analgesic efficacy. In agreement with our data, Kim et al [ 16 ] found no opioid sparing efficacy and pain scores were lower only at 1 h after a single-dose RSB block but not thereafter compared with control group with no block.…”
Section: Discussionsupporting
confidence: 93%
“…Studies on the preemptive effect of RSB in patients undergoing laparoscopic surgery are limited, and some are contrary to our results. First, Kim et al reported that bilateral RSB decreased the intensity of superficial pain only during the first hour after robotic cholecystectomy, compared with a placebo group [35]. Second, Jin et al reported that there was no significant difference in the pain, analgesic requirements, or time to first rescue analgesic after transabdominal gynecological surgery between the pre-RSB and post-RSB groups [36].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Gurnaney et al were confirmed by the work of Kim and colleagues, who compared 2 groups of adult patients who underwent robotic cholecystectomies. They found that the RSA group had better pain scores, lower doses of opioid requirements, and higher satisfaction scores ( 17 ). The finding of Kamei and colleagues did not differ so much when they used RSA in a group of patients who underwent single incision laparoscopic cholecystectomies; they emphasized that analgesia could have lasted for 6 hours postoperatively ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can provide adequate postoperative analgesia in 97% of patients in their trial that aimed at detection of the local anesthetic spread and the effectiveness for surgical anesthesia of RSA ( 26 ). Unlike the previously mentioned trials ( 16 , 17 , 24 - 26 ), we used extended duration RSA for postoperative 72 hours through catheter embedded in rectus sheath bilaterally after completion of surgeries. There is lack of sufficiently designed prospective randomized controlled trials that compare the opioid sparing properties of extended time RSA against placebo or TEA ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation